2018
DOI: 10.1534/g3.118.200631
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Structural Variations Within Five Continental Populations of Drosophila melanogaster

Abstract: Chromosomal structural variations (SV) including insertions, deletions, inversions, and translocations occur within the genome and can have a significant effect on organismal phenotype. Some of these effects are caused by structural variations containing genes. Large structural variations represent a significant amount of the genetic diversity within a population. We used a global sampling of Drosophila melanogaster (Ithaca, Zimbabwe, Beijing, Tasmania, and Netherlands) to represent diverse populations within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…It has been shown that the fixation rate of an allele in a nonrecombining chromosome is dependent on how deleterious the allele is, with highly deleterious mutations having a lower fixation rate than mutations that are less deleterious (Kaiser and Charlesworth 2010). Given the relative rarity of large indel polymorphisms outside the supergene region, and the low frequencies of large indels in other species (Sudmant et al 2015; Long et al 2018), we can assume that large insertions and deletions generally have a higher fitness cost than point mutations. Deletions are generally thought to be more deleterious than insertions because they involve the complete removal of genetic information, an assumption that is supported by the lower frequency of standing variation in deletions than insertions in human populations (Sudmant et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the fixation rate of an allele in a nonrecombining chromosome is dependent on how deleterious the allele is, with highly deleterious mutations having a lower fixation rate than mutations that are less deleterious (Kaiser and Charlesworth 2010). Given the relative rarity of large indel polymorphisms outside the supergene region, and the low frequencies of large indels in other species (Sudmant et al 2015; Long et al 2018), we can assume that large insertions and deletions generally have a higher fitness cost than point mutations. Deletions are generally thought to be more deleterious than insertions because they involve the complete removal of genetic information, an assumption that is supported by the lower frequency of standing variation in deletions than insertions in human populations (Sudmant et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…While most of our knowledge so far comes from analyses based on short-read sequencing, long-read sequencing technologies are starting to be applied to Drosophila species including D. melanogaster [42,43]. These so-called third generation sequencing techniques hold promise for incorporating the knowledge on other types of genomic variants, such as structural variants to our current understanding of the evolution of D.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Recently, Faddeeva-Vakhrusheva et al (3) showed that a complete assembly of Wolbachia could be generated as a by-product of assembling the genome of a Wolbachia -infected arthropod species using PacBio long-read sequences. Based on this observation, we attempted to generate complete Wolbachia assemblies using long-read shotgun sequencing data for three geographically distinct Drosophila melanogaster lines (I23 from Ithaca, NY; N25 from the Netherlands; and ZH26 from Zimbabwe) (4) that were previously identified by Early and Clark (5) as being infected with variants of the Wolbachia strain w Mel. These flies were reared on a diet of 10% yeast, 10% glucose, and 1% agar at 25°C (J. Chaston, personal communication).…”
Section: Announcementmentioning
confidence: 99%